APPLICATIONS OF MAXWELL'S EQUATIONS IN MODERN MEDICAL TECHNOLOGIES (Web of Teachers: Inderscience Research, 2026)
Maxwell's equations are the mathematical foundation of classical electromagnetism and describe how electric and magnetic fields are generated, interact, and propagate through matter. In modern medicine, these equations are not only theoretical principles but also practical tools used in the design, optimization, and safety evaluation of diagnostic and therapeutic devices. Magnetic resonance imaging, transcranial magnetic stimulation, electroporation-based therapy, radiofrequency ablation, and biomedical monitoring systems all depend on electromagnetic field behavior in biological tissues. This article analyzes the role of Maxwell's equations in selected medical technologies, explains the relevant physical mechanisms, and summarizes their biomedical significance through equations and comparative tables. The analysis shows that Maxwell's equations support image formation, neural stimulation, controlled tissue heating, targeted intracellular delivery, and medical device safety assessment. Therefore, electromagnetic theory remains essential for the development of accurate, safe, and effective medical technologies.